Growing up Muslim Muslim college students in America tell their life stories - Garrod, Andrew; Kilkenny, Robert (Cornell University Press, 2014)
The Introduction by Eboo Patel. In Growing Up Muslim, Andrew Garrod and Robert Kilkenny present fourteen personal essays by college students of the Muslim faith who are themselves immigrants or are the children of immigrants to the United States. In their essays, the students grapple with matters of ethnicity, religious prejudice and misunderstanding, and what is termed Islamophobia.